Discovery of imidazo[1, 2-a]-pyridine inhibitors of pan-PI3 kinases that are efficacious in a mouse xenograft model. Issue 3 (1st February 2016) - Han, Wooseok; Menezes, Daniel L.; Xu, Yongjin; Knapp, Mark S.; Elling, Robert; Burger, Matthew T.; Ni, Zhi-Jie; Smith, Aaron; Lan, Jiong; Williams, Teresa E.; Verhagen, Joelle; Huh, Kay; et al.
Graphical abstract: Abstract: Alterations in PI3K/AKT signaling are known to be implicated with tumorigenesis. The PI3 kinases family of lipid kinases has been an attractive therapeutic target for cancer treatment. Imidazopyridine compound1, a potent, selective, and orally available pan-PI3K inhibitor, identified by scaffold morphing of a benzothiazole hit, was further optimized in order to achieve efficacy in a PTEN-deleted A2780 ovarian cancer mouse xenograft model. With a hypothesis that a planar conformation between the core and the 6-heteroaryl ring will allow for the accommodation of larger 5′-substituents in a hydrophobic area under P-loop, SAR efforts focused on 5′-alkoxy heteroaryl rings at the 6-position of imidazopyridine and imidazopyridazine cores that have the same dihedral angle of zero degrees. 6′-Alkoxy 5′-aminopyrazines in the imidazopyridine series were identified as the most potent compounds in the A2780 cell line. Compound14 with 1, 1, 1-trifluoroisopropoxy group at 6′-position demonstrated excellent potency and selectivity, good oral exposure in rats and in vivo efficacy in A2780 tumor-bearing mouse. Also, we disclose the X-ray co-crystal structure of one enantiomer of compound14 in PI3Kα, confirming that the trifluoromethyl group fits nicely in the hydrophobic hot spot under P-loop.